Detection of sildenafil and sildenafil analogues in coffee powder using liquid chromatography tandem mass spectrometry [electronic resource] - Zareen Sofia Onn, 1987-; Abdul Rahim Yacob (2014)
Thesis (Sarjana Sains (Kimia)) - Universiti Teknologi Malaysia, 2014